GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 29156 species occurrences available in GBIF matching the query: TaxonKey: Ambrosia L.. The dataset includes 29156 records from 374 constituent datasets: 5 records from Bioimages. 2 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 92 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 2 records from Guadeloupe_Herbier. 6 records from JOI - Herbário Joinvillea. 338 records from OEH Atlas of NSW Wildlife. 198 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 324 records from Botanical Society of the British Isles - Vascular Plants Database. 6 records from HUEM - Herbário da Universidade Estadual de Maringá. 3 records from HUFU - Herbarium Uberlandense. 193 records from Phanerogamic Botanical Collections (S). 1 records from Inventory and BioBlitz Records from rare Charitable Research Reserve. 3 records from PRECIS (KwaZulu-Natal Herbarium). 41 records from University of Vienna, Institute for Botany - Herbarium WU. 3 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 1 records from Extra-andean Patagonian Herbarrium -CONICET- Argentina. 10 records from IAC - Herbário do Instituto Agronômico de Campinas. 13 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 9 records from Herbarium Vonderau - FULD. 715 records from Naturalis Biodiversity Center (NL) - Botany. 3 records from SPSF - Herbário Dom Bento José Pickel. 42 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 49 records from PRECIS. 4 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 2 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 7 records from SANT herbarium vascular plants collection. 2 records from UFP - Herbário UFP - Geraldo Mariz. 20 records from Colección Herbario Federico Medem Bogotá - FMB. 54 records from FLORIVON. 5 records from Herbario Pontificia Universidad Javeriana. 49 records from ICN - Herbário do Instituto de Ciências Naturais. 43 records from Herbario Universidad de Antioquia (HUA). 78 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 33 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 428 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 28 records from The digitization of plant specimens of NTU. 76 records from Phytochorologie des départements français. 3 records from SMDB - Santa Maria Departamento de Biologia. 3 records from BioFokus. 11 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 5 records from Colección Herbario Universidad Católica de Oriente. 359 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 26 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 2 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 2 records from CESJ - Herbário Leopoldo Krieger. 2 records from Irish Vascular Plant Data - Paul Green. 558 records from FlorKart - FlorenKartierung Gefaesspflanzen. 1 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 31 records from Plantae of Costa Rica (INBio). 1198 records from Artdata. 74 records from MBM - Herbário do Museu Botânico Municipal. 28 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 9 records from Herbario Museo de La Salle Bogotá (MLS). 1 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 57 records from OHN. 57 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 11 records from Données ONF Faune-Flore-Fonge. 3 records from FCAB - Herbário Friburguense. 14 records from Tallinn Botanic Garden. 10 records from Plant (KIWE-PL). 43 records from Herbarium areqvipense (HUSA). 2 records from BRFC Black Rock Forest Consortium Herbarium. 283 records from Australia's Virtual Herbarium. 92 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 1 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 11 records from Herbier de Strasbourg. 66 records from Vascular Plant Herbarium, UiB. 50 records from Kathryn Kalmbach Herbarium. 12 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 9 records from Natural History Museum Maastricht (NL) - Herbarium. 3923 records from Consortium of California Herbaria. 229 records from iNaturalist Research-grade Observations. 3 records from UCBG TAPIR Provider. 1 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 91 records from CONN. 15 records from HUCS - Herbário da Universidade de Caxias do Sul. 2 records from Registros biológicos de especies de plantas del Bosque Seco en Colombia presentes en el Herbario JBGP. 76 records from H.A. Stephens Herbarium. 1 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 31 records from University of Lethbridge Herbarium (LEA). 218 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 2 records from Estonian Museum of Natural History. 107 records from University of California Museum of Paleontology. 17 records from ALCB - Herbário Alexandre Leal Costa. 1 records from HUSC - Herbário Unisanta. 2 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 4 records from HPBR - Herbário Padre Balduino Rambo. 6 records from Estonian University of Life Sciences. 2 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 2 records from A common plants survey of vascular plants in South Northumberland and Durham, United Kingdom. 243 records from NMNH occurrence DwC-A. 1 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 1 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 32 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 16 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 226 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 1 records from LUSC - Herbário de Lages da Universidade do Estado de Santa Catarina. 58 records from OAC-BIO Herbarium. 2 records from VIC - Herbário da Universidade Federal de Viçosa. 1 records from Colección preservada Jardín Botánico de la Patagonia Extraandina. 2 records from Naturhistorisches Museum Mainz, Herbarium Oesau. 3 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 2 records from Herbario de la Universidad de Granada: GDA. 68 records from naturgucker. 2 records from Field Museum of Natural History (Botany) - Historical Photographs of Type Specimens from Berlin (B). 1 records from The Flora of County Wexford. 55 records from Dutch Vegetation Database (LVD). 63 records from INPN - Données flore des CBN agrégées par la FCBN. 1 records from seed. 11 records from UEC - Herbário da Universidade Estadual de Campinas. 5 records from FUEL - Herbário da Universidade Estadual de Londrina. 1 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 120 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 89 records from Herbario IEB del Instituto de Ecología, A.C., México (IE-BAJíO). 196 records from Herbario del CIBNOR. 16 records from Vascular plant specimens of Akita Prefectural Museum. 24 records from Vascular plants database of Atugi City Museum. 1 records from Jardin botanique de Montréal (JBM). 14 records from FKSE-Herbarium specimens of Faculty of Symbiotic Systems Science, Fukushima University, Japan. 1 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 20 records from Plant (KIWE-PL). 26 records from Plant (JNHM-PL). 1 records from Plant (SMNH-PL). 2 records from Plant (NHMC-PL). 4 records from Plant (NSMK-PL). 1 records from Herbaria of the University and ETH Zürich. 7 records from Tiroler Landesmuseum Ferdinandeum. 4 records from IBF Monitoring of Vascular Plants. 2 records from Vascular plant specimens of Iida City Museum. 1 records from BSBI tetrad data for Ireland. 1389 records from Tropicos Specimen Data. 4 records from Botanical Research Intitute of Texas. 29 records from Natural History Museum (London) Collection Specimens. 148 records from Natural History Museum, Vienna - Herbarium W. 56 records from Actualización de la base de datos del Herbario de la Universidad de Sonora (USON). 17 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 2 records from Flora polínica de las llanuras de Sonora, al sur de Hermosillo. 3 records from Lista florística preliminar de Tamaulipas. 3 records from Flora del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 10 records from Florística de la reserva de la biósfera de Mapimí. 61 records from NatureServe Network Species Occurrence Data. 30 records from Base de datos del Herbario de la Unidad Académica de Agronomía de la Universidad Autónoma de Zacatecas. 4 records from Flora-On: occurrence data of the flora of mainland Portugal. 4 records from Flora de la reserva de la biósfera de los Pantanos de Centla, en el estado de Tabasco, México. 2 records from Flora de las Barrancas del Cobre. 5 records from Plantas exóticas del centro de México y obtención de imágenes para una flora virtual de malezas. 190 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 7 records from Formación del banco de datos del herbario (UCAM). 48 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 1 records from Catálogos florísticos de México por entidad federativa e información etnobotánica de la Colección del Herbario Nacional Biól. Luciano Vela Gálvez (INIF). 3 records from Florística de áreas protegidas en el estado de Durango. 10 records from Base de datos sobre la flora de Durango. 1 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 1 records from Catálogo y base de datos preliminar de la flora de Sinaloa. 2 records from Flora acuática vascular y de zonas inundables del área de protección de flora y fauna Laguna de Términos, Campeche, México. 9 records from Dataflos. 1 records from Leiner-Herbar Konstanz. 7 records from Universität Salzburg. 20 records from Australian National Herbarium (CANB). 3 records from Fungal Biodiversity Centre (CBS) - Fungi strains. 2 records from Royal Museum of Central Africa - Metafro-Infosys - Prelude. 1 records from Factual Database of Native Flora Seeds in Korea. 70 records from Canadian Museum of Nature Herbarium. 73 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 32 records from Fairchild Tropical Botanic Garden Virtual Herbarium Darwin Core format. 18 records from The AAU Herbarium Database. 7 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 13 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 33 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 5 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 10 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 6 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 7 records from Aranzadi Zientzi Elkartea. 1 records from CIBIO, Alicante:ABH-GBIF. 1 records from Herbario EMMA. Herbario de la Escuela Técnica Superior de Ingenieros de Montes. UPM. 27 records from Herbario de la Universidad de Sevilla. 3 records from Herbario de la Universidad de Sevilla, SEV-Historico. 1 records from Dpto de Botánica, Ecología y Fisiología Vegetal (Herbario COFC). Facultad de Ciencias. Universidad de Córdoba. 4 records from Institut Botanic de Barcelona, BC. 1 records from HerbarioHerrerense. 1 records from Auckland Museum Botany Collection. 4 records from Herbarium of Jyväskylä University Museum. 17 records from Royal Botanical Gardens Herbarium. 1 records from DAO Herbarium Type Specimens. 8 records from Paleobiology Database. 20 records from herbario. 69 records from Plant Specimens of Kurashiki Museum of Natural History. 6 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 1 records from Herbarium of Kitakyushu Museum of Natural History and Human History. 53 records from Vascular Plant Collection. 754 records from Arizona State University Vascular Plant Herbarium. 5 records from Botanical Museum, Copenhagen. Database of type specimens. 140 records from DAV UC Davis Center for Plant Diversity. 56 records from California State University, Chico. 26 records from Herbarium (UNA). 1 records from MEXU/Herbario Los Tuxtlas. 86 records from MEXU/Asteraceae. 101 records from NSW herbarium collection. 1 records from CBS Filamentous Fungi Database. 42 records from Herbarium Berolinense. 1182 records from Observations du Conservatoire botanique national du Bassin parisien.. 52 records from Biologiezentrum Linz. 47 records from Herbarium Senckenbergianum Görlitz (GLM). 5 records from United States National Plant Germplasm System Collection. 75 records from USU-UTC Specimen Database. 1 records from Institut Botanic de Barcelona, BC-Histórico. 17 records from Herbarium de Geo. B. Hinton, México. 214 records from Botanical Society of the British Isles - Vascular Plants Database additions since 2000. 1 records from Angiosperm specimens of Iwate Prefectural Museum. 24 records from Vascular Plants Collection of Sagamihara City Museum. 203 records from Harvard University Herbaria. 88 records from Specimen Database of Colorado Vascular Plants. 14 records from BioGIS - Vascular plants - A. Danin's grid database. 6 records from inatura - Erlebnis Naturschau Dornbirn. 23 records from EURISCO, The European Genetic Resources Search Catalogue. 22 records from Plant specimens depodited in Osaka Museum of Natural History, Japan.. 2 records from Kochi Prefectural Makino Botanical Garden. 1 records from MEXU/Colección Histórica. 30 records from Biodiversitätsdatenbank des Landes Salzburg. 212 records from Herbario de la Universidad de Arizona, EUA. 742 records from Repatriación de datos del Herbario de Arizona (ARIZ). 2 records from Agentes Bioactivos de Plantas Desérticas de Latinoamérica (ICBG). 490 records from Programa de repatriación de datos de ejemplares mexicanos. 2 records from Árboles de la Península de Yucatán, Flora del Distrito de Tehuantepec, Oaxaca y Familia Asteraceae en México (IBUNAM). 212 records from Oklahoma Vascular Plants Database Provider. 23 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from Walldorf-Wiesloch: "Natur über den Gleisen". 187 records from USF Herbarium. 16 records from Plantae, TAIF (Taiwan e-Learning and Digital Archives Program, TELDAP). 23 records from Natural History Museum, University of Tartu. 2 records from Herbarium of Umeå University (UME). 14 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 49 records from Field Museum of Natural History (Botany) Seed Plant Collection. 2 records from BOTU - Herbário Irina Delanova Gemtchújnicov. 44 records from Belgian IFBL Flora Checklists (1939-1971). 6 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 308 records from New Mexico Biodiversity Collections Consortium database. 1 records from Perchtoldsdorfer Heide. 58 records from Colorado State University Herbarium. 38 records from EKY_Darwincore. 184 records from MISS_DC_01MAR2006. 42 records from NCSU_Darwincore. 1135 records from UA Herbarium. 566 records from R. L. McGregor Herbarium Vascular Plants Collection. 10 records from Banco de Datos de la Biodiversidad de la Comunitat Valenciana. 3 records from Colección de plantas vasculares de Brasil del Herbario "Jaime Andrés Rodríguez". LEB-Brasil. 116 records from Vascular Plant Specimen Database of Kanagawa Prefectural Museum of Natural History. 9 records from Gunma Museum of Natural History, Vascular Plant Specimen. 31 records from Vascular plants collection of Hiratsuka City Museum. 3 records from MEXU/Colección de Plantas Acuáticas. 252 records from Plant. 4 records from MGC Herbarium of University of Malaga (Spain): MGC-Cormof dataset. 18 records from Biological and palaeontological collection and observation data MNHNL. 43 records from Botany Division, Yale Peabody Museum. 3 records from Paleobotany Division, Yale Peabody Museum. 18 records from Herbarium Senckenbergianum (FR). 6 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 18 records from Database of Native Plants in Taiwan. 5 records from University of Ghana - Ghana Herbarium. 15 records from Herbarium of Taiwan Forestry Research Institute. 4 records from Herbarium specimens of the Muséum d'Histoire Naturelle of Aix-en-Provence (AIX). 6 records from Herbario Amazónico Colombiano. 2 records from Plant - Seed (KIDR-PL). 31 records from Precis Plant Data. 4 records from Monitoring records of plant species in the Hakone region of Fuji-Hakone-Izu National Park, Japan, 2001-2010. 33 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 1 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 2 records from Vascular Herbarium, NMBU. 35 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 5 records from UPCB - Herbário do Departamento de Botânica. 26 records from Plant (JNHM-PL). 262 records from ArtenFinder. 105 records from Lund Botanical Museum (LD). 61 records from VegetWeb - Repositorium von Vegetationsaufnahmen a. 5 records from Geographically tagged INSDC sequences. 1 records from Registros biológicos en áreas protegidas obtenidos de documentos impresos. 1 records from HTSA - Herbário do Trópico Semiárido. 1 records from Plant (SMNH-PL). 24 records from Norwegian Species Observation Service. 11 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 1 records from HST - Herbário Sérgio Tavares. 2 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 1 records from Colección de Herbario. 1 records from Caracterización florística de las ciénagas en Gamarra y Barrancabermeja de 2012. 1163 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Herbier_CNSF. 68 records from Bernice P. Bishop Museum. 2 records from FURB - Herbário Dr. Roberto Miguel Klein. 75 records from Carnet en Ligne. 1 records from CRI - Herbário Pe. Dr. Raulino Reitz. 9 records from EcoRecord - Vascular plant records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 19 records from ENDEMIC SPECIES RESEARCH INSTITUTE（Herbarium）. 6 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 2 records from Seed collection – Dead seeds for evaluation and observation purposes. 1 records from The Flora of County Wexford. 23 records from Colección del Herbario PSO de la Universidad de Nariño. 3 records from UFACPZ - Herbário da Universidade Federal do Acre. 220 records from Royal Botanic Garden Edinburgh Herbarium (E). 77 records from Michigan State University Herbarium Vascular Plants. 42 records from Botany (UPS). 218 records from Instituto de Ciencias Naturales. 4 records from Museu de Ciències Naturals de Barcelona: BGJBB. 152 records from Herbier du Québec (QUE) – Collection de plantes vasculaires. 1 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1 records from Inventaire National du Patrimoine Naturel : Flore d'Ille-et-Vilaine. 1 records from JPB - Herbário Lauro Pires Xavier. 5 records from EAC - Herbário Prisco Bezerra. 2 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 14 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 3 records from Herbario de la Universidad Industrial de Santander. 1 records from Institut Menorquí d'Estudis. Colección Histórica de Rodríguez Femenías, Herbarium Generale Minoricae: HGM-Femenias. 63 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 4 records from Tromsø Museum, Vascular plants. 7 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 5 records from BHCB - Herbário da Universidade Federal de Minas Gerais. 12 records from Vascular Plant Herbarium, Trondheim (TRH). 11 records from Données ONF Faune-Flore-FOnge. 29 records from Institute of Ecology and Evolutionary Biology, National Taiwan University. 1 records from Vascular Plants, Field notes, Oslo (O). 1671 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 7 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 1 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 4 records from Plant (NSMK-PL). 1 records from Digital Florula - Palo Verde Biological Station. 5 records from UB - Herbário da Universidade de Brasília. 39 records from Green Plant Herbarium (TRT). 1 records from Inventaire National du Patrimoine Naturel : Flore du Massif Armoricain. 1 records from Sheffield Biological Records Centre - Sheffield Biological Records Centre- Non-sensitive Records from all taxonomic groups.. 3 records from PEUFR - Herbário Professor Vasconcelos Sobrinho. 15 records from Instituto de ciencias naturales. 4 records from HCF - Herbário da Universidade Tecnológica Federal do Paraná Campus Campo Mourão. 10 records from Herbier CNRST/INERA. 1 records from Miscellaneous Vascular Plants. 3 records from Herbario virtual bosques secos de Colombia - sección herbario FMB (IAvH). 168 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 9 records from Allan Herbarium (CHR). 3 records from IRAI - Herbário do Parque da Ciência Newton Freire Maia. 1 records from Botanical Society of the British Isles - Changing Flora of Glasgow 1982-2000. 11 records from SysTax - Botanical Gardens. 4 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 4 records from Shropshire Ecological Data Network - Shropshire Ecological Data Network Database. 56 records from Flore de Franche-Comté. 4 records from HPL - Herbário do Jardim Botânico Plantarum. 1 records from BoBO - Botanic Garden and Botanical Museum Berlin-Dahlem Observations. 3 records from CEN - Herbário da Embrapa Recursos Genéticos e Biotecnologia. 1 records from Colección Nacional de Actuopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 315 records from Vascular Plant Herbarium, Oslo (O). 2 records from Occurrences in SinBIOTA. 33 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 2 records from Anymals+plants - Citizen Science Data. 18 records from Natural History Museum Rotterdam (NL) - Plantae collection. 28 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 36 records from E. C. Smith Herbarium (ACAD). 55 records from BUT Friesner Herbarium. 2 records from The Flora of County Waterford. 5 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 9 records from Herbarium Erlangense. 2 records from EAN - Herbário Jaime Coelho de Moraes. 8 records from BioGIS - Vascular plants - SPNI. 5 records from SysTax - Herbaria. 15 records from IPA - Herbário - IPA Dárdano de Andrade Lima. 45 records from Geneva Herbarium – General Collection (G). 185 records from Instituto de Botánica Darwinion. 18 records from Nijmegen Natural History Museum (NL) - Herbarium. 3 records from SJRP - Herbário de São José do Rio Preto. 1 records from Greater Manchester Ecology Unit - Higher Plant Records From Greater Manchester. 6 records from Bristol Regional Environmental Records Centre - BRERC October 2009. 721 records from CAS Botany (BOT). 4 records from Atlas des plantes vasculaires de Lorraine. 8 records from CPAP - Herbário CPAP. 1 records from BHZB - Herbário do Jardim Botânico da Fundação Zoo-Botânica de Belo Horizonte. 1 records from MOSS - Herbário Dárdano de Andrade Lima. 1 records from HRCB - Herbário Rioclarense. 49 records from PACA-AGP - Herbarium Anchieta.
Keywords: GBIF; biodiversity; species occurrences